Analisis Perbandingan Perhitungan Harga Pokok Penjualan Gremii dan Mizaplus terhadap Nilai Persediaan - Agustiawan, Agustiawan; Julianti, Windi (Universitas Nahdlatul Ulama Surabaya, 2024)
The aim of this research is to analyze the comparison of methods for calculating the cost of goods sold for Gremmi and Mizaplus. This research is descriptive quantitative research. This research uses secondary data, namely financial reports. The analysis results show that the HPP calculation using the Average method is higher than the FIFO method. The results of a lower cost of goods sold using the FIFO method will result in high profits for the continuity of the company's operations